Objemové ztráty - Feldová, Petra (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Cílem této práce je vyhodnocení ztrátových průtoků těsnícími spárami a posouzení vlivu expanzních komůrek různých tvarů, umísťujících se do nich za účelem snížení objemových ztrát. První část shrnuje teoretické poznatky o hydrogenerátorech, které nejvíce trpí na tyto ztráty. Jsou zde také popsána analytická řešení proudění ve spárách a možnosti využití simulačních programů jako je Fluent pro vyšetřování složitějších úloh. Výpočtová část obsahuje porovnání analyticky určených hodnot objemových průtoků pro proudění v hladké spáře s hodnotami získanými z programu Fluent. Díky těmto hodnotám je možné také posoudit vliv rotace na průtoky, neboť analytické vztahy tento vliv nepostihují. Pro snazší porovnání proudění v expanzních dutinách jsou dále vykresleny v jejich průřezu kontury statického tlaku, vektory rychlosti a proudnice.

The main goal of this bachelor thesis is to evaluate the flow of sealing gaps and assess the impact of the expansion chambers of various shapes , placing them in order to reduce volumetric losses . The first section summarizes theoretical knowledge of pumps, which suffer the most from these losses. There are also described the analytic solutions of flow in the cracks and possible use of simulation programs, such as Fluent, for investigation of more difficult tasks. The computational part compares analytically determined values of the volume flow for smooth gap, with the values obtained from the program Fluent. Thanks to the values from this program is also possible to assess the effect of rotation on the flows. Analytical relationships do not include this impact . For easier comparison the flow in the expansion chambers are further drawn contours of the static pressure, velocity vectors and pathlines in their cross-section.
Volumetric losses
Keywords: Objemové ztráty; hydrogenerátory; expanzní dutiny; těsnící spáry; volumetrická účinnost; CFD analýza; Volumetric losses; pump; expansion chambers; sealing gaps; volumetric efficiency; CFD analysis